Mastering English: A Comprehensive Guide to Learning, Speaking and Teaching Effectively for University Student - Widhi, Bidari Andaru; Alawiyah, Rosidah; Elthia, Memy Wardani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research guide to learning, speaking, and teaching effectively for university students has a purpose to improve students speaking skill and used qualitative descriptive which data from interviews 3 students on some university. It discusses about mastering English exactly on speaking skills in university. In the university, students must possess English standards or English proficiency the teacher only delivers material and topics in writting, and it is difficult to imagine. In this case, the researcher tries to explain the gap in information activities of students speaking skills. The students who answer the interview and tried to describe 3 topics on the cards some of them continuously transferred the written and oral and several of them had barrier such as vocabularies, pronunciation, grammar, accent. In the classroom use communication language teaching approach that mean student center as learner and guide so is the topic from them, the teacher is only as control the role of class. Student has success for communication and build up the vocabularies, accent, grammatical and pronunciation are similar with foreigner